The protective effect of spironolactone and role of the Na+/K+-ATPase pump on intestinal ischemia/reperfusion injury - VELİOĞLU ÖĞÜNÇ, AYLİZ; ÇETİNEL, ŞULE (MARMARA UNIV, 2018)
The aim of this study was to evaluate the possible protective effect of spironolactone (SPL) and role of the Na-K ATPase pump on intestinal ischemia/reperfusion injury. In our study, the period of ischemia was established by clamping the mesenteric artery for 45 minunder anesthesia in Wistar albino rats and the animals left for reperfusion at the end of this period were decapitated after one hour. Spironolactone (20 mg kg(-1)) was administered orally for three days before ischemia, 30 minbefore ischemia. The control group rats were subjected to the Sham operation and administered saline solution. TNF-alpha and IL-1 beta levels were measured in the serum samples. Ileal Na+/K+-ATPase, myeloperoxidase (MPO) analysis were performed. Structural injury was assessed histopathologically. Ischemia/reperfusion increased serum TNF-alpha and IL-1 beta levels together with MPO activity, whereas these values were maintained at the control group levels through SPL activation. However, ischemia/reperfusion decreased Na+/K+-ATPase activity in ileal tissues; however, these parameters were found to be significantly increased with SPL activation. The protective effect of SPL against ischemia/reperfusion injury by different mechanisms, mainly the activity of the Na+/K+-ATPase pump, suggests that this nontoxic agent may constitute a new clinical therapeutic principle.
Keywords: Intestinal ischemia/reperfusion; inflammation; Na+/K+-ATPase; spironolactone; ISCHEMIA-REPERFUSION INJURY; OXIDATIVE STRESS; NITRIC-OXIDE; RATS; MODEL; MYELOPEROXIDASE